Preservasi Ovarium dan Pengaruhnya Terhadap Morfologi Folikel Domba - Rosadi, Bayu; Agus Setiadi, Mohamad; Sajuthi, Dondin; Boediono, Arief (Jurnal Veteriner; Vol 12, No 2 (2011))
The purpose of this study was to evaluate the effect of cooling and freezing of ewes ovarian tissue ontheir follicles morphology. The study was carried out in two experiments. Experiment I, ovaries weremaintained in Phosphate Buffered Saline (PBS) at -20oC and room temperature (RT) for 24 h, and at 5oCfor 24 h and 72 h, respectively. After storage, follicles were histologically evaluated. Experiment II, theovarian cortex was isolated and tissue slices (±1 mm3) were prepared. Following this tissues were loadedinto hemistraw then transferred to equilibration solution (PBS+20% FBS+7,5% EG+7,5 % DMSO) atroom temperature and held for 10, 20, 30 minutes, respectively. Afterward tissues were tranferred tovitrification solution (PBS+20%FBS +15%EG+15%DMSO ) for 3 minutes, then the hemistraw was placeddirectly into liquid nitrogen. After thawing, the tissues were prepared for histological examination. All ofthe follicles were deteriorated after 24 h storage at RT. The percentage of morphologically normal follicleswas significantly reduced when ovarian tissues were stored at -20oC for 24 h and at 5oC for 24 h and 72 h.However, it seemed to have a minor deterioration effect when the tissues were kept at 5oC for 24 h(P<0.05). Antral follicles were damaged in all of the treatments. Primordial follicles preserved theirmorphology intactness better than growing follicles. Exposing tissues to equilibration medium for 10minutes seemed to produce higher numbers of morphologically normal follicles (P<0.05), compared towhen tissues were exposed for 20 minutes and 30 minutes (P>0.05). It can be concluded that exposingtissues to equilibration solution for 10 minutes prior to freezing would kept the ovarian follicles morphologyin good condition.
Keywords: ovarium, follicle, preservation, vitrification, ewe